Pengaruh Lingkungan Kerja, Kecerdasan Emosional, dan Motivasi Kerja terhadap Produktivitas Kerja - Angelita, Aisyah Lucky; Rozamuri, Arif Murti (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
This study examines how work environment, emotional intelligence, and motivation affect employee productivity among Generation Z in Jakarta. Concerns regarding relatively low and inconsistent productivity among younger employees highlight the importance of identifying key factors that influence their performance. However, previous studies have largely examined these variables independently, with limited emphasis on their combined effects on Generation Z employees. This study addresses this gap by integrating organizational and psychological factors into a single analytical model. A quantitative survey was conducted involving 115 Generation Z employees in Jakarta. Data were gathered using systematically designed questionnaires and subsequently processed and examined through the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings indicate that work environment, emotional intelligence, and motivation each demonstrates a positive and statistically significant effect on work productivity. Simultaneously, these variables play a role in enhancing productivity across different work settings. This study provides empirical evidence that improving work environment quality, strengthening emotional intelligence, and enhancing motivation are critical factors in increasing the productivity of Generation Z employees.